An Integrative Neurocircuit Perspective on Psychogenic Nonepileptic Seizures and Functional Movement Disorders: Neural Functional Unawareness. (January 2015) - Perez, David L.; Dworetzky, Barbara A.; Dickerson, Bradford C.; Leung, Lorene; Cohn, Rachel; Baslet, Gaston; Silbersweig, David A.
Functional neurological disorder (conversion disorder) is a neurobehavioral condition frequently encountered by neurologists. Psychogenic nonepileptic seizure (PNES) and functional movement disorder (FMD) patients present to epileptologists and movement disorder specialists respectively, yet neurologists lack a neurobiological perspective through which to understand these enigmatic groups. Observational research studies suggest that PNES and FMD may represent variants of similar (or the same) conditions given that both groups exhibit a female predominance, have increased prevalence of mood-anxiety disorders, frequently endorse prior abuse, and share phenotypic characteristics. In this perspective article, neuroimaging studies in PNES and FMD are reviewed, and discussed using studies of emotional dysregulation, dissociation and psychological trauma in the context of motor control. Convergent neuroimaging findings implicate alterations in brain circuits mediating emotional expression, regulation and awareness (anterior cingulate and ventromedial prefrontal cortices, insula, amygdala, vermis), cognitive control and motor inhibition (dorsal anterior cingulate, dorsolateral prefrontal, inferior frontal cortices), self-referential processing and perceptual awareness (posterior parietal cortex, temporoparietal junction), and motor planning and coordination (supplementary motor area, cerebellum). Striatal-thalamic components of prefrontal-parietal networks may also play a role in pathophysiology. Aberrant medial prefrontal and amygdalar neuroplastic changes mediated by chronic stress may facilitate the development of functional neurological symptoms in a subset of patients. Improved biological understanding of PNES and FMD will likely reduce stigma and aid the identification of neuroimaging biomarkers guiding treatment development, selection, and prognosis. Additional research should investigate neurocircuit abnormalities within and across functional neurological disorder subtypes, as well as compare PNES and FMD with mood-anxiety-dissociative disorders.